Prospective Life Cycle Assessment of High-Temperature Superconductors for Future Grid Applications - Buchholz, Alexander (Karlsruher Schriftenreihe zur Supraleitung, 2022)
High-temperature superconductors have distinct advantages compared to conventional conductors. Below their critical temperature, superconductors have immeasurably low ohmic losses. To maintain the superconducting state, superconductors require constant cooling. This study aims at identifying the environmental impacts of the application of superconductors in future grid technologies such as superconducting power cables.